2014
DOI: 10.1002/cssc.201402925
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Catalyst Pore Structure and Acid Properties on the Dehydration of Glycerol

Abstract: Hierarchical porous catalysts have recently attracted increasing interest because of the enhanced accessibility to active sites on such materials. In this context, previously reported hierarchically mesoporous ASN and ASPN materials are evaluated by applying them to the dehydration of glycerol, and demonstrate excellent catalytic performance. In addition, a comprehensive understanding of the effects of pore structures and the acid properties on the reaction through comparative studies with microporous HZSM-5 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 52 publications
3
32
0
Order By: Relevance
“…Many literature papers have reported that acrolein could be produced from glycerol via a catalytic gas phase dehydration process. 16,[20][21][22][23][24][25][26][27][28][29] The recent development of glycerol to acrolein over different acid catalysts, such as zeolites, metal oxides, and heteropolyacids (HPAs) supported on metal oxides, and the effects of catalyst pore structure and acid properties on the dehydration of glycerol have been reviewed and well documented. 16,20,21 Dubois et al synthesized pyridines by a two-step method that included: (1) glycerol dehydration to acrolein, acrolein enrichment and separation, and (2) reaction of the acrolein from the preceding step with the additional acetaldehyde to form pyridines.…”
Section: Introductionmentioning
confidence: 99%
“…Many literature papers have reported that acrolein could be produced from glycerol via a catalytic gas phase dehydration process. 16,[20][21][22][23][24][25][26][27][28][29] The recent development of glycerol to acrolein over different acid catalysts, such as zeolites, metal oxides, and heteropolyacids (HPAs) supported on metal oxides, and the effects of catalyst pore structure and acid properties on the dehydration of glycerol have been reviewed and well documented. 16,20,21 Dubois et al synthesized pyridines by a two-step method that included: (1) glycerol dehydration to acrolein, acrolein enrichment and separation, and (2) reaction of the acrolein from the preceding step with the additional acetaldehyde to form pyridines.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the above reason, the superior catalytic results of our HCP-based solid acid catalysts are also related to the nano-confinement effect depicted in Scheme 2. In the case of small pore size, only a limited amount of substrate molecules such as cyclohexanone oxime can be accommodated within the inner pore space, promoting the efficient collision of the substrate to the acidic site on the pore wall, which thereby accelerates the reaction [57][58][59]. By contrast, in the case of broad pores, the substrate not only attacks the acid site on the pore wall to proceed catalysis, but also can randomly cross the pore channel without react with acid sites, which causes a low catalytic efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent publication, Yi et al reported different aluminosilicate materials with different pore diameters and acidity for the dehydration of glycerol into acrolein. 178 Hierarchically mesoporous acidic aluminosilicate (ASN-X) and aluminosilicophosphate (ASPN-X, X = Si/Al molar ratio) with identical pore structures but different acid sites were tested and their activities were compared to those of microporous (HZSM-5) and mesoporous (AlMCM-41) aluminosilicate acid catalysts. The unique features of ASN and ASPN materials enabled elucidating how the reaction was governed by the combined action of pore structures and acid sites in the catalysts.…”
Section: Zeolitesmentioning
confidence: 99%